Pelatihan Menulis dan Membaca Aksara Bali dalam Media Lontar di Museum Lontar Dukuh Penaban, Desa Adat Dukuh Penaban, Kecamatan Karangasem, Kabupaten Karangasem - I Kadek Widiantana; A.A.Diah Indrayani; Gek Diah Desi Sentana; I Nyoman Ranem; Gede Agus Budi Adnyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Balinese language, script, and literature are important knowledge that must be mastered by Balinese people, and Balinese ancestors have also inherited thousands of Lontar manuscripts that should be known because they are full of noble values. However, with abundant of literary heritages, only a few people have the interest and ability to write, read, or study the contents of the Lontar. Efforts are needed from an early age, in order to prepare regeneration that is able to maintain and develop the knowledge stored in the Lontar manuscripts. Based on the above background, the dedication of the Department of Religious Language and Literature Education in the 2021 fiscal year will be carried out at the Lontar Dukuh Penaban Museum, Dukuh Penaban Customary Village, Karangasem Sub-district, Karangasem Regency. The method implemented in relation to the Balinese Literacy Writing and Reading Training in Lontar Media at the Lontar Dukuh Penaban Museum, Dukuh Penaban Customary Village, Karangasem Sub-district, Karangasem Regency is a training method. At the beginning, the service team gave an explanation in advance about